2013
DOI: 10.1111/jdv.12139
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of frontal fibrosing alopecia and lichen planopilaris: a systematic review

Abstract: Frontal fibrosing alopecia (FFA) is a primary lymphocytic cicatricial alopecia with characteristic clinical pattern of progressive frontotemporal hairline recession, perifollicular erythema and hyperkeratosis and symptoms of itch and burning, occurring mainly in post-menopausal women. FFA is considered a subtype of lichen planopilaris (LPP), based on their identical histopathology. Currently, no evidence-based treatment is available for FFA. Our aim was to determine the effectiveness of available treatment opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
151
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(169 citation statements)
references
References 50 publications
5
151
0
13
Order By: Relevance
“…half of the cases (42%) using systemic steroid. In some studies, daily administration of oral prednisolone of 25-50 mg in short term was reported to be more beneficial (26). Steroids were found to be less efficacious in FFA than LPP.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…half of the cases (42%) using systemic steroid. In some studies, daily administration of oral prednisolone of 25-50 mg in short term was reported to be more beneficial (26). Steroids were found to be less efficacious in FFA than LPP.…”
Section: Discussionmentioning
confidence: 99%
“…FFA progresses slowly and the progression stops spontaneously over time, therefore, organizing the treatment and assessing the treatment response may be difficult (2)(3)(4). As the alopecia is cicatricial, the aim should be stopping the progression of the disease, preventing more alopecia and decreasing the symptoms (2,26). Also, there is no clear consensus on how to assess the efficacy of FFA treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations